Stockpile life of foam stabilised material and the implications for labour intensive construction - Chasi, Brian Takaona (My University, 1998)
Various studies have been done to show that labour-based construction can meet the high standards normally required in the construction of roads. The organisational requirements that were needed to ensure the efficient use of labour have also been dealt with in various studies. Tile need for alleviation of poverty, unemployment and the negative social impact thereof by increasing the labour input in construction is understood by all concerned. A further step is however necessary before the idea of increasing the . labour component in any kind of roadwork can be taken seriously. Engineers need to move forward from the policy and organisational issues associated with labour intensive construction and start to provide designers with sound and innovative engineering solutions to overcome the hurdles experienced on the ground. The study looks at the process of foam bitumen stabilisation of soils and gravels with a view of utilising this innovative method for labour intensive construction. The material after having been stabilised can be placed in a stockpile. Actual durations that the material can safely remain in stockpile have been determined in this study to be in excess of six months for recycled asphalt and in excess of four months for the foam stabilised sand. Foam stabilised gravel was also studied and showed that after a year in stockpile the material failed probably due to a weakening of the bitumen and aggregate bond. Covering the stockpiled material did not show any significant difference to that of a similar uncovered stockpile. The position within the stockpile also did not have much effect on the engineering properties of the stoc piled material. The fact that the foam stabilised material can be worked on when cold and that it can be stockpiled for several months implies that the material is labour friendly and can be used in labour intensive construction of road base course layers or wearing course layers.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering. Johannesburg 1998.
Keywords: Roads--Design and construction; Foamed materials; Soil stabilization; Public Service employment